Using research networks to generate trustworthy qualitative public health research findings from multiple contexts - Nyirenda, Lot; Kumar, Meghan Bruce; Theobald, Sally; Sarker, Malabika; Simwinga, Musonda; Kumwenda, Moses; Johnson, Cheryl; Hatzold, Karin; Corbett, Elizabeth L.; Sibanda, Euphemia; Taegtmeyer, Miriam (BMC, 2022)
This article was published in BMC Medical Research Methodology [ © The Author(s). 2020 Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/).] and the definite version is available at: https://doi.org/10.1186/s12874-019-0895-5 The Journal's website is at: https://bmcmedresmethodol.biomedcentral.com/articles/10.1186/s12874-019-0895-5